Prevalence of atopic dermatitis, asthma and rhinitis from infancy through adulthood in rural Bangladesh: a population-based, cross-sectional survey - Samir K Saha; Gary L Darmstadt; Courtney J Pedersen; Mohammad J Uddin (BMJ Open)
Objective Describe the pattern of atopic disease prevalence from infancy to adulthood.Design Cross-sectional household survey.Setting Community-based demographic surveillance site, Mirzapur, Bangladesh.Participants 7275 individuals in randomly selected clusters within 156 villages.Primary and secondary outcome measures The 12-month prevalence of atopic dermatitis (by UK Working Party Criteria (UK criteria) and International Study of Asthma and Allergies in Childhood (ISAAC)), asthma and rhinitis (by ISAAC); disease severity (by ISAAC); history of ever receiving a medical diagnosis.Results Children aged 2 years had the highest prevalence of atopic dermatitis—18.8% (95% CI 15.2% to 22.4%) by UK criteria and 14.9% (95% CI 11.6% to 18.1%) by ISAAC— and asthma (20.1%, 95% CI 16.4% to 23.8%). Prevalence of rhinitis was highest among 25–29 year olds (6.0%, (95% CI% 4.5 to 7.4%). History of a medical diagnosis was lowest for atopic dermatitis (4.0%) and highest for rhinitis (27.3%) and was significantly associated with severe disease compared with those without severe disease for all three conditions (atopic dermatitis: 30.0% vs 11.7%, p=0.015; asthma; 85.0% vs 60.4%, p<0.001; rhinitis: 34.2% vs 7.3%, p<0.001) and having a higher asset-based wealth score for asthma (29.7% (highest quintile) vs 7.5% (lowest quintile), p<0.001) and rhinitis (39.8% vs 12.5%, p=0.003). Prevalence of having >1 condition was highest (36.2%) at 2 years and decreased with age. Having atopic dermatitis (ISAAC) was associated with significantly increased odds ratios (OR) for comorbid asthma (OR 5.56 (95% CI 4.26 to 7.26)] and rhinitis (3.68 (95% CI 2.73 to 4.96)). Asthma and rhinitis were also strongly associated with each other (OR 8.39 (95% CI 6.48 to 10.86)).Conclusions Atopic disease burden was high in this rural Bangladeshi population. Having one atopic condition was significantly associated with the presence of another. Low incidence of ever obtaining a medical diagnosis highlights an important opportunity to increase availability of affordable diagnosis and treatment options for all age groups.